The AST/ALT ratio predicts survival and improves oncological therapy decisions in patients with non-small cell lung cancer receiving immunotherapy with or without radiotherapy - Zhang, Yanyan; Zhang, Jingxin; Shang, Shijie; Ma, Jiachun; Wang, Fei; Wu, Meng; Yu, Jinming; Chen, Dawei (Frontiers in Oncology, 2024)
Abstract Background and purpose Immunotherapy, with or without radiotherapy (iRT or ICIs-nonRT), is the standard treatment for non–small cell lung cancer (NSCLC). Nonetheless, the response to the treatment varies among patients. Given the established role of aspartate aminotransferase/alanine transaminase (AST/ALT) ratio in predicting cancer prognosis, we sought to identify whether the pre-treatment AST/ALT ratio has the potential to serve as a prognostic factor for NSCLC patients receiving ICIs-nonRT and iRT. Materials and Methods We retrospectively analyzed NSCLC patients who received immunotherapy between April 2018 and March 2021. Patients were classified into iRT group and ICIs-nonRT group and further classified based on AST/ALT ratio cut-off values. The Kaplan-Meier (KM) method estimated the time-to-event endpoints (progression-free survival (PFS) and overall survival (OS) Results Of the cohort, 239 underwent ICIs-nonRT and 155 received iRT. Higher AST/ALT ratios correlated with worse outcomes in the ICIs-nonRT group but indicated better outcomes in those who received iRT. Multivariate analysis validated AST/ALT ratio as an independent prognostic factor. For AST/ALT ratios between 0.67-1.7, both ICIs-nonRT and iRT yielded similar treatment outcomes; with AST/ALT ratios greater than 1.7, iRT could be a more favorable treatment option (P=0.038). Conversely, for ratios less than 0.67, ICIs-nonRT could be a more favorable treatment option (P=0.073). Conclusions The pre-treatment AST/ALT ratio demonstrates potential as a prognostic marker for treatment outcomes in NSCLC patients receiving either ICIs-nonRT or iRT. This finding could help guide clinicians in selecting more effective treatment protocols, thereby enhancing patient prognosis. .